Bicyclist Crash Types on National, State, and Local Levels: A New Look. Issue 6 (June 2019) - Thomas, Libby; Nordback, Krista; Sanders, Rebecca
This paper presents an overview of prevalent bicyclist crash types in the United States, providing insights for practitioners that may be useful in planning safer networks and taking other proactive and risk-based approaches to treatment. The study compares fatal bicyclist crash types from national data with serious injury and all-severity bicyclist collisions from the state of North Carolina (NC) and the city of Boulder, Colorado. Overall, bicyclist fatalities in the United States are more prevalent in urban areas (69%) than rural areas (29%). Though the majority of all-severity crashes are at intersections, most fatal and disabling injury bicyclist crashes occur at non-intersection locations, including nearly one-third of bicyclists who die from collisions involving overtaking motorists. Top intersection crash types across national fatal and all-severity crashes in NC and Boulder include bicyclists failing to yield and motorists turning across a bicyclist's path. However, many of the top all-severity types in the two jurisdictions differ from the top fatal crash types nationwide. These comparisons provide a fresh look at bicyclist crash type trends and have potential importance with respect to planning safer networks for Vision Zero communities, since a key finding is that locations and crash types most prevalent among fatal and serious injuries may differ from the most prevalent types for all-severity crashes. The findings could be useful to agencies lacking their own resources for risk-based assessment, but also suggest it is important to analyze higher severity crash types and jurisdiction-specific data when possible.